2017
DOI: 10.18203/2349-3933.ijam20175181
|View full text |Cite
|
Sign up to set email alerts
|

A correlative study to evaluate the gestational age by sonological measurement of placental thickness in normal second and third trimester pregnancy

Abstract: Original Research ArticleA correlative study to evaluate the gestational age by sonological measurement of placental thickness in normal second and third trimester pregnancy Sujit Pant 1 , Sunita Dashottar 2 * INTRODUCTIONAccurate knowledge of the Gestational Age (GA) is important for the good antenatal care and the successful deliveries of babies. The most useful information provided by the obstetrics ultrasound is the accurate determination of the gestational age. 1 As significant numbers of pregnant women a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Most of the antenatal women were primipara i.e. 53% whereas parity ranged from 0-3 which is comparable with the other studies [9,10] . The mean placental thickness had no correlation with age group (p value 0.487 nonsignificant).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Most of the antenatal women were primipara i.e. 53% whereas parity ranged from 0-3 which is comparable with the other studies [9,10] . The mean placental thickness had no correlation with age group (p value 0.487 nonsignificant).…”
Section: Discussionsupporting
confidence: 89%
“…It was observed that mean placental thickness at a particular gestation had no correlation with parity and the p value was non-significant (0.258). Pant et al [9] also found no correlation between parity and placental thickness.…”
Section: Discussionmentioning
confidence: 93%
“…In the study done by Pant et al the mean placental thickness for groups with gestational age in weeks 14-20, 21-25, 26-30, 31-35 were 18.35, 23.62, 28.88 and 32.62 mm respectively which almost correspond to the mid-points of the gestational age. 6 Jain et al in their study observed that the mean placental thickness increased with advancing gestational age, almost matching from 27-33 weeks of gestation. 7 In the present study, there was progressive increment in placental thickness till term in par with the gestational age.…”
Section: Discussionmentioning
confidence: 83%
“…In the earlier study by Pant et al the placental thickness almost increased parallel with the placental thickness till 35weeks of gestation after which it falls by 1-3mm than the gestational age. 6 In the study by Grannum et al there was a gradual decrease in the placental thickness after 32weeks of gestation till term. 8…”
Section: Discussionmentioning
confidence: 94%
“…Placental thickness correlates with gestational age in the second and third trimesters and may be used as an alternative method for the evaluation of latter. [5] We conducted this study to evaluate the correlation between placental thickness and gestational age.…”
Section: Introductionmentioning
confidence: 99%